Lingkungan dan Pemukiman Zaman Kerajaan Majapahit dalam CGI (Computer Generated Imagery) - Ardiyansah Ardiyansah; Ardiyan Ardiyan; Satrya Mahardhika (Humaniora, 2010)
Majapahit is believed to be a great civilization that once have been victorious in our archipelago. Although much is known about the Majapahit, but it turns out more obscure facts have not been revealed and need to be explored in more depth. One is how the people of Majapahit live their life, how they built the civilization by building houses and how they manage their social environment. Using CGI (Computer Generated Imagery) Technology a "replica" Majapahit life can be built by combining the findings of archaeological and engineering-based digital animation 3d.